"Virtual dual sourcing" of specialized goods: Lessons from supply chain disruption of Riken and Epson Atmix. Issue 1 (5th December 2018) - Mukai, Yuichiro; Fujimoto, Takahiro; Park, Young Won
Abstract : Purpose: The purpose of this paper is to examine how the Japanese firms who make customized goods respond to supply chain failure caused by natural disaster, and shows the process and problem to build virtual dual sourcing with relation to product/process architecture. Design/methodology/approach: Two case studies of Japanese manufacturing firm have been discussed. The research team had extensive site visits of major Japanese export industries (such as automotive, electronics, chemical and so on). The firms were carefully selected based on three criteria: the firms had major disaster-related damages; the senior executives of firms were willing to share their experiences and allow the research team to visit the sites; selected firms were notified in advance about the research perspective of how best to resume the flow of design information to customers speedily and effectively. Findings: The main finding of this research is that visualizing design information of products is an essential step for virtual dual sourcing strategy or effective recovery from supply chain disruption, even if there is limitation because of its product/process architecture. Substituting other production line is not an absolute condition for contingent action. Balancing contingent activity and competitiveness is important for firms and building "virtual dual sourcing" system is one of the effective ways of business continuity plans (BCP). Research limitations/implications: The researchers would imply that if product/process architecture is modular, visualizing design information for virtual dual sourcing is not so difficult. If product/process architecture is integral, visualizing design information for virtual dual is likely to be incomplete because it needs tacit knowledge for operation. Specifying and smoothly dispatching key persons with tacit knowledge would be effective for recovery from supply chain disruption. However, there still remain limitations in this research, for it is uncertain how much visualizing design information and virtual dual sourcing are effective in response to product/process architecture. Practical implications: The researchers would imply that key persons with tacit knowledge should be dispersed for compensation of visualization of design information. Originality/value: The originality of this research shows supply chain risk and recovery from the design information view of manufacturing. With real cases of the two companies having experience of natural disaster, this paper shows the process and problem to build virtual dual sourcing system, and shows balancing competitiveness and contingent activity.